The Effect of Project Based Addictive Substance Learning on Critical Thinking Skills of Junior High School Students - Safitri, Erica Meilia; Sudarti, Sudarti; Handayani, Rif’ati Dina; Jamhari, Mohammad; Haeruddin, Haeruddin (Jurnal Pendidikan MIPA, 2023)
Abstract: Critical thinking is one of the 4C competencies that is important for students to master to support their success in the learning process. The purpose of this research is to determine the effect of the project based learning (PjBL) model on students' critical thinking skills. The method used is purposive sampling. This type of research is quasi-experimental with a nonequivalent control group design (pre-test and post-test). The average results of the two samples are known through the independent sample t-test. The difference in critical thinking skills scores between the control class and the experimental class will be known through a parametric independent sample t-test with a sig value. > 0.05 which means homogeneous. If tcount > table resulting from the right-sided t-test then it can be said that HO is rejected and Ha is accepted, meaning the learning model used in the experimental class has a significant influence. In the research that has been carried out, it is known that the project based learning (PjBL) model has a significant effect on students' critical thinking skills, which is known through the difference in the average scores of the control class and the experimental class. Keywords: critical thinking skills, learning model, PjBL model. Abstrak: Berpikir kritis menjadi salah satu kompetensi 4C yang penting untuk dikuasai peserta didik agar menunjang keberhasilannya dalam proses pembelajaran. Tujuan dilakukannya penelitian ini untuk mengetahui pengaruh model pembelajaran project based learning (PjBL) terhadap keterampilan berpikir kritis peserta didik. Metode yang digunakan yaitu purposive sampling. Jenis penelitian ini yaitu kuasi eksperimen dengan desain penelitian nonequivalent control group design (pre-test dan post-test). Hasil rata-rata kedua sampel diketahui melalui independet sample t-test. Perbedaan skor keterampilan berpikir kritis antara kelas kontrol dan kelas eksperimen akan diketahui melalui uji parametrik independent sample t-test dengan nilai sig. > 0,05 yang berarti homogen. Jika thitung > tabel yang dihasilkan dari uji t-pihak kanan maka dapat dikatakan bahwa HO ditolak dan Ha diterima berarti model pembelajaran yang digunakan di kelas eksperimen memiliki pengaruh yang signifikan. Pada penelitian yang sudah dilakukan diketahui bahwa model pembelajaran project based learning (PjBL) berpengaruh dengan signifikan terhadap keterampilan berpikir kritis peserta didik yang diketahui melalui perbedaan rata-rata nilai kelas kontrol dan kelas eksperimen.  Kata kunci: model pembelajaran, model PjBL, keterampilan berpikir kritis. DOI: http://dx.doi.org/10.23960/jpmipa/v24i4.pp859-866